Silk degumming time controls horseradish peroxidase-catalyzed hydrogel properties. (1st July 2020) - Sahoo, Jugal Kishore; Choi, Jaewon; Hasturk, Onur; Laubach, Isabel; Descoteaux, Marc L.; Mosurkal, Shreyas; Wang, Boyang; Zhang, Nina; Kaplan, David L.
Abstract : We report a fundamental study on effect of different silk degumming time on biomaterial properties of enzymatically crosslinked hydrogels. Abstract : Hydrogels provide promising applications in tissue engineering and regenerative medicine, with silk fibroin (SF) offering biocompatibility, biodegradability and tunable mechanical properties. The molecular weight (MW) distribution of SF chains varies from ∼80 to 400 kDa depending on the extraction and purification process utilized to prepare the protein polymer. Here, we report a fundamental study on the effect of different silk degumming (extraction) time (DT) on biomaterial properties of enzymatically crosslinked hydrogels, including secondary structure, mechanical stiffness, in vitro degradation, swelling/contraction, optical transparency and cell behaviour. The results indicate that DT plays a crucial role in determining material properties of the hydrogel; decrease in DT increases β-sheet (crystal) formation and mechanical stiffness while decreasing degradation rate and optical transparency. The findings on the relationships between properties of silk hydrogels and DT should facilitate the more rational design of silk-based hydrogel biomaterials to match properties needed for diverse purpose in biomedical engineering.